Study of Current Cybersecurity Threats to Information & Operational Technology (IOT) and their Effect on e-Governance in Nepal - Bhagat, Chandran Kumar (Journal of UTEC Engineering Management, 2023)
As the development of digitalization process spreads worldwide, daily necessity and dependability on World Wide Web is increasing. Now after global pandemic of Coronavirus disease (COVID-19), digitalization has become compulsory process in the world. The process of digitization in Nepal is also increasing. Along with the process of digitization in Nepal, there is also a huge possibilities of cyber security threat. Today, the information security system must be set up to counter emerging vulnerabilities that may additionally arise as a result of technological development and advancement. In the complex and dynamic arena of Internet, the challenges inherent in protecting Information infrastructure is significantly increasing, maybe as an influence of the global existence of services etc. Depending on these networks. These network links are unprotected to cyber-attacks due to more than a few flaws in the system. Therefore, it is necessary to accelerate on the protection that covers the software and infrastructure to provide the governance fruitful interconnection besides any probable hazard of being arranged. This research tries to find out the cyber security problems in the present concern as technological innovation is moving each and every sphere of existence so as e-Governance applications. Research additionally emphases on how e-Governance is made more protected and what type of security and protection mechanism to be implemented, have to be safe, tightly closed and dependable surroundings via numerous technologies in digital Governance functions i.e. cloud computing, e-commerce, social networking, e-Banking/Internet Banking system, e-Payment and also outline here in what way to reduce the Online crimes through strengthening the safety components of e-Governance systems.